FENOMENA PEMAHAMAN DAN PENERAPAN HAKIKAT MAKNA KATA KEJAHATAN DAN PELANGGARAN DALAM PERKEMBANGAN HUKUM - Hamsir, Hamsir (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2020)
The word crime and violation in the legal phenomenon of society experiences distortion when reviewing sanctions from the act. The word crime means that sanctions are classified as severe, whereas violations are assumed to contain mild sanctions. In further legal developments, legal acts / legal events or offenses are identified with just one word, namely "criminal acts", both those charged with acts that are philosophically crimes or those philosophically charged with violations. By knowing the fundamental differences between the separation of crime and violation with a philosophical approach, the community will have a strong basis for applying the law (academic "theoretical" and "practical" and or for the compiler, "legislative law"). Acts, events, offenses or "Straafbaarfeit" crimes in straafrecht, sub-system of criminal offenses, and sub-criminal offenses. Therefore, uniting these two things into "criminal acts" only, contrary to the underlying thought and moral foundations. There are two factors that influence people's understanding of the nature of the meaning of the word crime and violation, namely: 1) Internal factors, the inability to interpret the meaning of the essence contained in these two things; 2). External factors, namely the existence of intentions to overturn the term for the sake of pragmatic interests and the inadvertence due to sources of information, news, literature, legislation that do not often mention and use these two terms in various legal events that occur in society.